Model indicators of physical and special physical fitness of 11-13 year-old freestyle wrestlers in the Republic of Sakha (Yakutia) at the sports specialization stage - Efimov, A.A.; Ponomarev, V.V.; Molukova, S.R. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to theoretically substantiate and develop model indicators of physical and special physical fitness for freestyle wrestlers aged 11-13 in the Republic of Sakha (Yakutia) and to recommend them for use in sports training. Methods and structure of the study. The study was conducted at the Amga Children's and Youth Sports School for Freestyle Wrestling in the Republic of Sakha (Yakutia) between 2022 and 2024. Thirty-one people aged 11-13 who were involved in freestyle wrestling at the stage of sports specialisation took part in the scientific work. Over the course of two years, systematic testing of the physical and special physical fitness indicators of the participants was organised and conducted. More than 300 measurements were taken for physical fitness and 450 measurements for special physical fitness. All this contributed to the collection of sufficient statistical material, on the basis of which, using methods of mathematical statistics (percentile scales), model indicators of physical and special physical fitness of freestyle wrestlers aged 11-13 years in the Republic of Sakha (Yakutia) were developed. Results and conclusions. The two-year study contributed to the collection of statistical data on the physical and special physical fitness of freestyle wrestlers aged 11-13 in the Republic of Sakha at the stage of sports specialisation. Physical fitness testing was conducted on five indicators, and special physical fitness testing on seven indicators. A total of 750 measurements were taken. The collected and compiled factual material made it possible to develop model indicators of physical and special physical fitness for freestyle wrestlers aged 11-13 in the Republic of Sakha. The developed model indicators can be recommended for use in the sports training of freestyle wrestlers aged 11-13 in the Republic of Sakha. All this will contribute to the effective and progressive process of sports training for freestyle wrestlers aged 11-13 in the region.